Detail specification for radio frequency coaxial connectors (series SMA). 50 ohms, unsealed, soldered, centre contact, clamp outer for flexible cables, solder outer for semi-rigid cables. Parameters. Full assessment level Part 3, (15th December 1985) - British Standards Institution,
No abstract available